FOUCAULT, POWER/KNOWLEDGE, AND ITS RELEVANCE FOR HUMAN RESOURCE MANAGEMENT - Townley, Barbara (Academy of Management Review, 1993)
Drawing on the work of Michel Foucault. I argue that human resource management (HRM) may be best understood as a discourse and set of practices that attempt to reduce the indeterminacy involved in the employment contract. Here I reread HRM practices from a Foucauldian power-knowledge perspective and suggest that this provides an avenue to reorient contemporary, historical, and comparative analyses of the area.